Measuring on Physiological Parameters and Its Applications: A Review - Hazzie Zati Bayani; Basari Basari (Universitas Ahmad Dahlan, 2024)
In providing patient care, it is essential to know the patient’s status to avoid incorrect treatment. Patient status includes various physiological parameters such as heart rate, blood oxygen saturation, blood pressure, body temperature, and respiratory rate. Measuring each physiological parameter requires data collection and analysis. Data acquisition in measuring physiological parameters can be categorized into contact methods, non-contact methods, invasive methods, and non-invasive methods. After data collection, it is crucial to analyze the collected data to ensure accurate and reliable measurements. This analysis can utilize RF signals, PPG signals, machine learning, and deep learning, depending on the specific needs and objectives of the study. This paper aims to identify studies based on types of data acquisition and analysis methods developed. These studies will be reviewed to understand the limitations of the data acquisition methods and analysis methods used. Additionally, this paper will discuss and classify the types of applications developed in these studies over the last five years, focusing on functionality, device design, and body-to-device connectivity. This review will identify whether the studies developed wearable or portable, wired or wireless devices, and their purpose whether for diagnosis, monitoring, or both. This review will also highlight the limitations and provide a brief perspective on future developments.